Dampak Verbal Bullying Terhadap Tingkat Kepercayaan Diri Siswa Kelas Tinggi Sekolah Dasar - Saputri, Devinna Andarini; Usman, Herlina; Wardhani, Prayuningtyas Angger (Universitas Muhammadiyah Magelang, 2024)
This study aims to determine the impact of verbal bullying on the level of self-confidence of upper class students at SDN Karet 04 Pagi. This research uses a qualitative case study method to research and understand problems in a limited context. This research uses triangulation to collect data through the process of observation, interviews and documentation. Research data analysis techniques that will be carried out include planning, implementation (data collection), data reduction, data presentation and drawing conclusions. Based on the results of research that has been conducted, the type of bullying that occurs most often is verbal bullying. The types of verbal bullying that are often carried out at SDN Karet 04 Pagi include mocking, insulting and other negative words that are demeaning to other people. The results of the data analysis that has been carried out show that the impact of verbal bullying at SDN Karet 04 Pagi experienced by victims is different for each student at the school.